2013
DOI: 10.3928/01477447-20130426-13
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Limb-length Discrepancy After THA: With and Without Computer Navigation

Abstract: Limb-length discrepancy following total hip arthroplasty (THA) is often cited as a reason for patient dissatisfaction and for hip instability. Various intraoperative techniques have been described to help restore normal limb length after THA. The purpose of this study was to assess whether a computer-navigated surgical technique would help restore limb-length equality following THA.A retrospective study of 150 consecutive patients compared a free-hand (non-navigated) THA technique vs a computer-navigated THA t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 6 publications
3
17
0
Order By: Relevance
“…A similar percentage of native acetabular anteversions were within the Lewinnek safe zone, while a higher percentage of native acetabular inclinations were within the safe zone than in previous data . Consistent with the literature , robot‐assisted THA showed higher accuracy and precision in positioning the cup within the safe zone than free‐hand THA (75% vs 36%), leading to a smaller number of outliers outside the safe zone in robot‐assisted THAs.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…A similar percentage of native acetabular anteversions were within the Lewinnek safe zone, while a higher percentage of native acetabular inclinations were within the safe zone than in previous data . Consistent with the literature , robot‐assisted THA showed higher accuracy and precision in positioning the cup within the safe zone than free‐hand THA (75% vs 36%), leading to a smaller number of outliers outside the safe zone in robot‐assisted THAs.…”
Section: Discussionsupporting
confidence: 83%
“…Component positioning in THA is critical in optimizing satisfactory clinical outcomes. Navigation THA has been reported to provide higher precision in component positioning than the conventional free‐hand THA . However, whether robot‐assisted THA better restores the 3D orientations and positions of the hip geometry remains unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For standard length stems, several studies have demonstrated that using a MIS approach does not compromise the long-term clinical and radiographic outcome when compared with conventional incision techniques [23,24]. With regard to the reconstruction of leg length, our results compare favorably with a report of Licini et al [25] who described 0.3-mm leg lengthening using navigation. This is the first study to describe the cup position with reference to the reported target orientation for inclination and anteversion using a MIS posterolateral approach in a large number of patients.…”
Section: Discussionsupporting
confidence: 80%
“…At 10 years, the clinical outcomes including the HSS, the HOOS, and the SF-12 were comparable in the two groups. In two previous studies (comparison of limb length discrepancy after THA: with and without computer navigation), no clinical difference was observed for the HHS or the Postel-Merle score between the CAS group and standard groups at, respectively, 1 year and 13 years [13,21]. To our knowledge, only one previous study used the HOOS as a specific hip quality-of-life questionnaire to compare the two techniques with no difference observed between the two groups at 5 to 7 years after surgery.…”
Section: Discussionmentioning
confidence: 76%